Meme factory cultures and content pivoting in Singapore and Malaysia during COVID-19 - Abidin, Crystal (2020)
This paper is a qualitative ethnographic study of how a group of meme factories in Singapore and Malaysia have adapted their content programming and social media practices in light of COVID-19. It considers how they have fostered, countered, or challenged the rise and spread of misinformation in both countries. More crucially, the paper considers how meme factories position their contents to speak in a variety of platformspecific and age-appropriate vernaculars to provide public service messaging or social critique to their followers.